2020
DOI: 10.1016/j.jjcc.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between surgical repair of aortic aneurysms and the diagnosis of subsequent cardiovascular diseases

Abstract: Cardiovascular diseases (CVDs) and aortic aneurysms (AAs) have several clinical risk factors and molecular signaling pathways in common. Several atherosclerotic risk factors, including hypertension, smoking, and hyperlipidemia, are shared between CVDs and AAs [1,2]. The prevalence of abdominal aortic aneurysm (AAA) in patients with acute myocardial infarction (AMI) could be as high as 3% [3]. Risk factors for AAA include age !65 years, a history of smoking, and previous coronary artery bypass grafting in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Reactive oxygen species are generated by endothelial cells during migraine attacks [ 11 , 12 , 13 ]. Consistent with previous studies, we also identified CAD and malignancy as risk factors for AAA development [ 42 , 43 , 44 ]. A previous study demonstrated an association between spontaneous coronary artery dissection (SCAD) and migraine.…”
Section: Discussionsupporting
confidence: 91%
“…Reactive oxygen species are generated by endothelial cells during migraine attacks [ 11 , 12 , 13 ]. Consistent with previous studies, we also identified CAD and malignancy as risk factors for AAA development [ 42 , 43 , 44 ]. A previous study demonstrated an association between spontaneous coronary artery dissection (SCAD) and migraine.…”
Section: Discussionsupporting
confidence: 91%